2002
DOI: 10.1124/jpet.102.041574
|View full text |Cite
|
Sign up to set email alerts
|

Injury Type-Specific Calcium Channel α2δ-1 Subunit Up-Regulation in Rat Neuropathic Pain Models Correlates with Antiallodynic Effects of Gabapentin

Abstract: The calcium channel ␣ 2 ␦-1 subunit is a structural subunit important for functional calcium channel assembly. In vitro studies have shown that this subunit is the binding site for gabapentin, an anticonvulsant that exerts antihyperalgesic effects by unknown mechanisms. Increased expression of this subunit in the spinal cord and dorsal root ganglia (DRG) has been suggested to play a role in enhanced nociceptive responses of spinal nerve-injured rats to innocuous mechanical stimulation (allodynia). To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
270
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(292 citation statements)
references
References 40 publications
18
270
0
1
Order By: Relevance
“…expression of 4 genes [Gadd45a (15), ATF3 (16,17), SmagP (18), and Cacna2d1 (19,20)] whose expression is altered by nerve injury, using RNA from the dorsal root ganglia of animals that received nerve blocks (n ϭ 4 in each group). As a positive control for local anesthetic-associated nerve injury that would be relevant to the formulations used here, 4 animals were given sciatic nerve blocks with 80 mM amitriptyline, a tricyclic antidepressant with local anesthetic properties that resembles bupivacaine in structure and mechanism of action (21), and that causes severe myotoxicity and neurotoxicity (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…expression of 4 genes [Gadd45a (15), ATF3 (16,17), SmagP (18), and Cacna2d1 (19,20)] whose expression is altered by nerve injury, using RNA from the dorsal root ganglia of animals that received nerve blocks (n ϭ 4 in each group). As a positive control for local anesthetic-associated nerve injury that would be relevant to the formulations used here, 4 animals were given sciatic nerve blocks with 80 mM amitriptyline, a tricyclic antidepressant with local anesthetic properties that resembles bupivacaine in structure and mechanism of action (21), and that causes severe myotoxicity and neurotoxicity (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…In support of these findings, a recent study has shown that selective blockade of LPAR 1 , using the antagonist AM095, attenuates CNS demyelination after contusive spinal cord injury in mice and improves locomotor recovery (Santos-Nogueira et al, 2015). In addition to demyelination, LPAR 1 mediates the upregulation of the α2δ1 Ca 2+ channel subunit and the γ-isoform of protein kinase C (PKCγ) in spinal cord (Inoue et al, 2004); both of which are well-established markers of NP (Luo et al, 2002;Weiner and Chun, 1999;Weiner et al, 2001). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 86%
“…For instance, the anti-nociceptive and anti-allodynic effectiveness of GBP has been widely supported by studies in animal models of many types of pain induced by peripheral nerve injury such as spinal nerve ligation [47][48][49][50], chronic compression injury [51][52][53][54][55][56] and spared nerve injury [57,58]. Moreover, GBP has also been demonstrated to have anti-allodynic and anti-hyperalgesic effects in animal models of diabetic neuropathy [29] and postherpetic neuralgia [59]. However, in our animal model of CPSP hypersensitivity, GBP delivered once daily via the intraperitoneal route only had a significant anti-allodynic effect during the first week of administration; GBP insensitivity occurred after the second week of treatment [20].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 99%
“…Experimentally, expression of a 2 d-1, but not a 2 d-2 (another binding site of GBP), is significantly increased in both the dorsal root ganglia (DRG) and the dorsal horn of the spinal cord in animal models of peripheral neuropathic pain. This up-regulation is thought to contribute to the development of allodynia and hyperalgesia [28][29][30][31]. It has thus been proposed that gabapentinoids alleviate neuropathic pain by blocking the trafficking of a 2 d-1 to the presynaptic terminals of DRG neurons and this subsequently leads to reduced Ca 2?…”
Section: Introductionmentioning
confidence: 99%